2011
DOI: 10.1016/j.jallcom.2010.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of intermetallic phases in overaged Zr-containing and Cr-containing Al–Zn–Mg–Cu alloys

Abstract: This paper investigates the effect of alloying elements on the characteristics of intermetallic phases in Zr-containing and Cr-containing 7xxx Al-Zn-Mg-Cu alloys at overaged conditions. Four Al-Zn-Mg-Cu alloy plates with different alloying element contents were studied by optical microscopy based image analysis, differential scanning calorimetry, scanning electron microscopy combined with energy disperse X-ray spectroscopy and transmission electron microscopy. The grain structures, recrystallisation, intermeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Addition of transition elements to high strength aluminum alloys enhances their mechanical properties. All the strengthening mechanisms of the high strength aluminum alloys depend primarily on precipitation hardening 10,11 . It is found that trace elements in aluminum can form a supplementary strengthening afforded in the most cases by dispersions which improve the recrystallization resistance and introduce a controlled amount of the strain 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Addition of transition elements to high strength aluminum alloys enhances their mechanical properties. All the strengthening mechanisms of the high strength aluminum alloys depend primarily on precipitation hardening 10,11 . It is found that trace elements in aluminum can form a supplementary strengthening afforded in the most cases by dispersions which improve the recrystallization resistance and introduce a controlled amount of the strain 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…High-strength thermally strengthened weldable alloys based on the Al-Zn-Mg system are used extensively for structural applications in aerospace industry [16][17][18][19], and recently reported to be alloyed with a small amount of copper, which improves considerably the resistance of the base metal and especially that of welded joints to corrosion cracking and slow disruption. Though the presence of copper intensifies the formation of hot cracks in welding of aluminum alloys, this drawback is eliminated by the introduction of a combined scandium and zirconium additive [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the development of aerospace technology, it is urgent to develop new aluminum alloys with better performance. Material workers have found that rareearth elements are of great importance to improve the service performance of Al-based alloys [6][7][8][9][10]. On a per-atom basis, scandium (Sc) has the greatest strengthening effect of any existing alloying addition to Al [11][12][13].…”
Section: Introductionmentioning
confidence: 99%